KOMUNIKASI INKLUSIF DALAM MERAWAT TRADISI LOKAL SEBAGAI STRATEGI PENGUATAN MODERASI BERAGAMA (STUDI KASUS DI DESA YOSOMULYO, KECAMATAN GAMBIRAN) - Agus Baihaqi; Agung Obianto; Afif Mahmudi (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Indonesian society has a very high level of plurality, both in terms of religion, ethnicity, and culture. This is actually an asset for development, but the threat of conflict is also very high. Religious moderation is an important prerequisite for achieving social harmony in a pluralistic society. Yosomulyo Village, Gambiran District, is known as a region where diverse religions and cultural backgrounds coexist relatively harmoniously. Residents build trust-based communication and consider religion a private matter. Meanwhile, togetherness as part of the community must be maintained as a form of preserving tradition. Residents recognize the plurality in their region and, through religious understanding, realize multiculturalism. This article aims to analyze the role of inclusive communication in preserving local traditions as a strategy to strengthen religious moderation in Yosomulyo Village. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation studies. The results indicate that local traditions nurtured through inclusive communication serve as a medium for interfaith social dialogue, strengthening tolerance, and preventing the polarization of religious identities. These findings confirm that communication based on local wisdom plays a significant role in building contextual and sustainable religious moderation. Keywords: inclusive communication, local traditions, religious moderation, Yosomulyo Village.